Urinary orosomucoid and retinol binding protein levels as early diagnostic markers for diabetic kidney Disease - Zhou, Xue-hong; Liu, Shu-yan; Yang, Bo; Li, Yong-feng; Hou, Bao-hua (BMC nephrology, 2023)
Diabetic kidney disease (DKD) is the most common microvascular complication of diabetes, which has been a major cause of end-stage renal failure. Diagnosing diabetic kidney disease is important to prevent long-term kidney damage and determine the prognosis of patients with diabetes. In this study, we investigated the clinical significance of combined detection of urine orosomucoid and retinol-binding protein for early diagnosis of diabetic kidney disease. We recruited 72 newly diagnosed patients with type 2 diabetes and 34 healthy persons from August 2016 to July 2018 at the First Affiliated Hospital of Henan Polytechnic University (Jiaozuo Second People's Hospital). Using the Mogensen grading criteria, participants were classified as having diabetes or diabetic kidney disease, and healthy persons constituted the control group. Urine orosomucoid and retinol-binding protein levels were measured and correlated with other variables. With the aggravation of renal damage, the level of urinary mucoid protein gradually increased. Urinary retinol-binding protein and microalbumin levels were significantly higher in the diabetes group than in control and nephropathy groups. Orosomucoid and retinol-binding protein might be independent risk factors for diabetes and diabetic kidney disease. Urinary orosomucoid significantly correlated with retinol-binding protein and microalbumin levels in the diabetic kidney disease group. Elevated urine orosomucoid and retinol-binding protein levels can be detected in the early stages of type 2 diabetic kidney disease. Both of these markers are important for diabetic kidney disease detection and early treatment.